The neural basis of cultural differences in delay discounting - Kim, Bokyung; Sung, Young Shin; McClure, Samuel M. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2012)
People generally prefer to receive rewarding outcomes sooner rather than later. Such preferences result from delay discounting, or the process by which outcomes are devalued for the expected delay until their receipt. We investigated cultural differences in delay discounting by contrasting behaviour and brain activity in separate cohorts of Western (American) and Eastern (Korean) subjects. Consistent with previous reports, we find a dramatic difference in discounting behaviour, with Americans displaying much greater present bias and elevated discount rates. Recent neuroimaging findings suggest that differences in discounting may arise from differential involvement of either brain reward areas or regions in the prefrontal and parietal cortices associated with cognitive control. We find that the ventral striatum is more greatly recruited in Americans relative to Koreans when discounting future rewards, but there is no difference in prefrontal or parietal activity. This suggests that a cultural difference in emotional responsivity underlies the observed behavioural effect. We discuss the implications of this research for strategic interrelations between Easterners and Westerners.